2020
DOI: 10.1371/journal.pone.0238192
|View full text |Cite
|
Sign up to set email alerts
|

Study of the spatial connection between urbanization and the ecosystem—A case study of Central Yunnan (China)

Abstract: This study provides new perspectives on urban development and conservation by exploring the spatial interaction between ecosystem services and urbanization. Limited studies have discussed the interaction between ecosystem services and urbanization; therefore, in this research, the spatial relationship between ecosystem services and urbanization is explored by taking the urban agglomeration in Central Yunnan as an example, and land-use data and economic and social data from 2009 and 2018 are used to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In a case study of Guangdong Province, Wang et al [ 27 ] explored the coupling of energy efficiency and urbanization, which finds that only Guangzhou and Shenzhen were in a high-coupling stage, while other cities in the province were undergoing low- and medium-coupling stages. Yang et al [ 28 ] found a significant correlation between the urbanization level and ecosystem service value in the urban agglomeration in Central Yunnan (China). Other studies have found that land and economic urbanization in the Pearl River Basin positively affected CO 2 emissions, while population urbanization reduced CO 2 emissions, and land use, industry production, output accumulation, and energy consumption patterns were the most significant influential factors [ 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a case study of Guangdong Province, Wang et al [ 27 ] explored the coupling of energy efficiency and urbanization, which finds that only Guangzhou and Shenzhen were in a high-coupling stage, while other cities in the province were undergoing low- and medium-coupling stages. Yang et al [ 28 ] found a significant correlation between the urbanization level and ecosystem service value in the urban agglomeration in Central Yunnan (China). Other studies have found that land and economic urbanization in the Pearl River Basin positively affected CO 2 emissions, while population urbanization reduced CO 2 emissions, and land use, industry production, output accumulation, and energy consumption patterns were the most significant influential factors [ 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cloud condensation nuclei may be responsible for the increase in precipitation in this region. Central Yunnan is one of the 19 urban agglomerations promoted by China in recent years, with a high urbanization rate [53]. The increase in precipitation in areas with a high urbanization rate may be mainly due to the increase in atmospheric buoyancy and convection-that is, atmospheric aerosols cause the increase in precipitation and precipitation intensity in the metropolitan area [54,55].…”
Section: Variation Characteristics Of Extreme Precipitation Indices In Yunnan During 1960-2019mentioning
confidence: 99%
“…The lowest level of ecosystem resilience is found in areas with urban development, and the state of low-value clustering is apparent (Figure S9). This indicates that the environmental problems and landscape fragmentation, brought about by the concentration of urban population and high-intensity development, are key factors influencing ecosystem health [47].…”
Section: Ecosystem Health Level Analysismentioning
confidence: 99%